A New Solution Method for Solving Transit Assignment Problems - Le, Luong Vuong (Advances in Engineering Research and Application, 2020)
Congested transit assignment problems are crucial sub problems in planning public transportation systems. These problems are usually formulated in the form of non-convex optimization programs. In this work, we investigate the model given by De Cea et al. [3] that has been widely used by both practitioners and researchers. For solving this model, to the best of our knowledge, one must use a diagonalization technique in order to yield a symmetric assignment problem before applying a solution method. Consequently, the quality of the obtained solution would be possibly affected. The motivation of our work is to find a new efficient solution method to tackle directly the original assignment problem without diagonalization techniques. Basing on DC programing, we introduce a new solution method. The proposed algorithm is tested on the data given in [3]. Comparing with the existing method, the experimental results show that our approach is promising.